Using a new Mobile Atmospheric Chamber (MACh) to investigate the formation of secondary aerosols from mobile sources: The case of gasoline direct injection vehicles. (July 2019) - Vu, Diep; Roth, Patrick; Berte, Tyler; Yang, Jiacheng; Cocker, David; Durbin, Thomas D.; Karavalakis, Georgios; Asa-Awuku, Akua
Abstract: Direct primary emissions from light-duty passenger in the past 50 years have been reduced significantly. However, the potential of primary emissions to oxidize downwind of sources is challenging and not well understood. This study investigates the secondary aerosol (SA) forming potential of emissions generated from four wall-guided gasoline direct injection (GDI) vehicles operating under realistic driving conditions. The exhaust for each vehicle was collected in the new University of California, Riverside, Center for Environmental Research and Technology's (CE-CERT) Mobile Atmospheric Chamber (MACh) while driven over vehicle test cycles using a chassis dynamometer and subsequently, photochemically aged. Results show that the chemical and physical properties of the aged aerosol are significantly different between the GDI vehicles and consistent within each vehicle's chamber experiment. Ageing modifies the particle composition, density, volatility, and cloud condensation nuclei (CCN) hygroscopicity. Secondary aerosol studies from controlled-laboratory dynamometer and atmospheric chamber studies will provide additional insight into the environmental impact of real-world vehicular sources. Highlights: Four gasoline direct injection vehicles produce distinct secondary organic and inorganic emissions profiles. Two of the four vehicles produced secondary inorganic aerosol, thereby modifying aerosol volatility and water-uptake. Emissions meet current primary standards (10mg/mi) but added secondary particle mass will not meet rigorous 3mg/mi levels.